Review of the genus Cassidinoma Hincks (Coleoptera: Chrysomelidae: Cassidinae: Omocerini) - Fernandes, Flávia Rodrigues; Borowiec, Lech (Zootaxa, 2013)
The Neotropical genus Cassidinoma Hincks is revised. A new synonymy is proposed: Cassidinoma denticulata (Boheman) = Cassidinoma monstrosa (Boheman) syn. n. The diagnosis, description, distribution, and biology are reviewed, and new distribution records are included. Illustrations of the habitus of adult and morphological structures are also added.